Endoscopic and Surgical Management of Intrabiliary Rupture of Hydatid Liver Cyst. (1st June 1992) - Leong, Sebastian; Kim, Young-In; Gray, Robin; Kortan, Paul; Haber, Gregory
Abstract : A man with hydatid disease complicated by intraabdominal cyst rupture 15 years earlier, presented with cholestatic jaundice. There was intrabiliary rupture of a hydatid liver cyst on endoscopic retrograde cholangiography. Sphincterotomy was performed allow clearance of hydatid material obstructing the bile ducts and insertion of a nasobiliary catheter for irrigation and drainage. Definitive surgery was performed. While endoscopic management is gaining recognition for relieving biliary obstruction in hydatid cystobiliary rupture, surgery is still required for patients who continue to pass hydatid debris obstructing the biliary tree and increasing the risk of cholangitis.